Cancionero : Songs of Laughter and Faith in New Mexico - Robb, J. D. (John Donald), 1892-1989 (Book collections on Project MUSE., 2015)
Composer John Donald Robb (1892-1989) built an invaluable legacy in the preservation of New Mexico's rich musical traditions. His extensive field recordings, compositions, papers, and photographs now comprise the John Donald Robb Archives in the University of New Mexico Libraries' Center for Southwest Research. Cancionero presents thirteen Hispanic folk songs from Robb's renowned archive. Created for musicians and vocalists, Cancionero features arrangements for voice with piano or guitar accompaniments as well as selected concert versions for voice, oboe, harp, and piano. Introductions include information about song forms, history, and subjects, providing further insight into each song.